Unified Response to COVID-19 Case Investigation and Contact Tracing, Chicago, December 2020–April 2021. (November 2022) - Kern, David; Tabidze, Irina; Modali, Laxmi; Stonehouse, Patrick; Karamustafa, Ayla
Objectives: We evaluated 2 innovative approaches that supported COVID-19 case investigation and contact tracing (CI/CT) in Chicago communities: (1) early engagement of people diagnosed with COVID-19 by leveraging the existing Healthcare Alert Network to send automated telephone calls and text messages and (2) establishment of a network of on-site case investigators and contact tracers within partner health care facilities (HCFs) and community-based organizations (CBOs). Methods: The Chicago Department of Public Health used Healthcare Alert Network data to calculate the proportion of people with confirmed COVID-19 who successfully received an automated telephone call or text message during December 27, 2020–April 24, 2021. The department also used CI/CT data to calculate the proportion of cases successfully interviewed and named contacts successfully notified, as well as the time to successful case interview and to successful contact notification. Results: Of 67 882 people with COVID-19, 94.3% (n = 64 011) received an automated telephone call and 91.7% (n = 62 239) received a text message. Of the 65 470 COVID-19 cases pulled from CI/CT data, 24 450 (37.3%) interviews were completed, including 6212 (61.3%) of the 10 126 cases diagnosed in HCFs. The median time from testing to successful case interview was 3 days for Chicago Department of Public Health investigators and 4 days for HCF investigators. Overall, 34 083 contacts were named; 13 117 (38.5%) were successfully notified, including 9068 (36.6%) of the 24 761 contacts assigned to CBOs. The median time from contact elicitation to completed notification by CBOs was <24 hours. Conclusions: Partnerships with HCFs and CBOs helped deliver timely CI/CT during the COVID-19 pandemic, suggesting a potential benefit of engaging non–public health institutions in CI/CT for existing and emerging diseases.